PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MENGGUNAKAN STRATEGI PEMECAHAN MASALAH DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) MATERI TEOREMA PYTHAGORAS - Imelda Dwiguna; Maimunah Maimunah; Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research was conducted due to limited mathematics learning devices to facilitate mathematical problem solving ability students. This research aims to produce mathematic learning instruments like syllabus, lesson plan (LP), student worksheet (SW), and assessment instrument using problem solving strategies in cooperative learning model student teams achievement division (stad) type for phytagorean theorm which valid and practicality. Development model used is 4-D model that consist of define, design, development and disseminate, but disseminate didn’t do because this purpose of study just produce devices which valid and practicality and got it on development step. Devices compiled was validated by three validators and revised based on the suggestions of validators. Based on the result of data analysis shows average score for syllabus are 3,67, LP are 3.86, SW are 3.87, and for assessment instrument are 3,57. Devices was categorized as very valid. Device was valeted are conducted two trials for a small group on 9 students in class VIII10 state junior high school 06 Pekanbaru only using SW and a large group on 37 students of class VIII6 state junior high school 06 Pekanbaru using LP and SW. The result of the analysis of practically in the learning device from theacher are 97,33%, for practically of the SW in the small group are 97,22%, and in the largegroup are 96,41% which was categorized as very practical.Key Words: Learning Devices, Problem Solving Strategies, Mathematical Problem Solving Ability